Ultrasound-guided stellate ganglion blockade – patient positioning is everything: a case report demonstrating the efficacy of a modified out-of-plane approach - Mo, Ke; Qian, Liang; Tian, Jingling; Liao, Junling; Tan, Fang; Kong, Weirong; Yu, Xianjun; Chi, Xinjin (Frontiers in Neuroscience, 2024)
Background Insomnia has become increasingly prevalent in modern society and is notoriously difficult to treat. Many patients exhibit a poor response to pharmacological interventions. Stellate ganglion block (SGB) has emerged as an effective method for managing insomnia; however, its efficacy may be compromised in some patients, primarily due to a variant vertebral artery anatomy. Case presentation This case report describes a patient with severe insomnia accompanied by anxiety. Through cervical ultrasound scanning, we identified richly branched cervical arteries at the C6−C7 segment of the vertebral artery, along with anatomical variations, which could pose a heightened risk for the traditional SGB procedure. Therefore, after carefully adjusting the patient’s positioning, we proceeded with ultrasound-guided SGB using a lateral paravein out-of-plane approach. Clinical signs of successful insomnia symptoms alleviation were consistently observed after each block utilizing this alternative technique multiple times in a single patient. Conclusion Our report reveals a new lateral paravein out-of-plane approach for ultrasound-guided SGB to treat insomnia, which might be considered an alternative method. More studies should be carried out to confirm the efficacy of this new approach.